2014
DOI: 10.1093/ageing/afu136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vertical and side-alternating vibration training on fall risk factors and bone turnover in older people at risk of falls

Abstract: whole-body vibration increased leg power and bone formation, but it did not provide any additional benefits to balance or fall risk factors beyond a falls prevention programme in older people at risk of falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 32 publications
1
55
1
1
Order By: Relevance
“…Chronic whole body vibration training has been shown to reduce markers of bone resorption [20, 21] and increase markers of bone formation [22] in a variety of populations. In the present study, there was a small increase in osteocalcin (~10%) 24 h after WBV and no change in bone resorption markers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic whole body vibration training has been shown to reduce markers of bone resorption [20, 21] and increase markers of bone formation [22] in a variety of populations. In the present study, there was a small increase in osteocalcin (~10%) 24 h after WBV and no change in bone resorption markers.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge only two studies have examined the acute effects of vibration training on bone turnover markers in adults but in both cases, VIB was performed prior to resistance training session, and therefore only the additive effects could be assessed. In both male [22] and female [23] participants, the addition of VIB training resulted in significant reductions in CTX concentration after the subsequent resistance training, but rather surprisingly bone resorption (serum Trap5b concentration) was significantly increased after VIB and resistance training in female participants. Bone formation (bone ALP) was not affected in either study, which is in contrast to the present study where VIB training alone did not alter bone resorption (CTX) but bone formation markers OC (all conditions) and P1NP (FG15 and FG60) were favorably affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although three previously published studies provided evidence of a significant therapeutic effect of vertical WBV on the TUG performance in elderly individuals (Bautmans et al, 2005;Bogaerts et al, 2011;Machado et al, 2010), recent studies did not report a significant effect on the same outcome, when WBV was compared to a no-training control group (Santin-Medeiros et al, 2015), an identical training program without WBV (Avelar et al, 2011;Corrie et al, 2015;Sitjà-Rabert et al, 2015), or a home balance exercise program (Sucuoglu et al, 2015). Four studies specifically evaluated the effect of vertical WBV on the BBS and Tinetti Balance Assessment and only Sucuoglu et al (2015) reported positive effects (Bautmans et al, 2005;Santin-Medeiros et al, 2015;Avelar et al, 2011;Sucuoglu et al, 2015).…”
Section: Lack Of Significant Effect Of Wbvmentioning
confidence: 99%
“…High levels of biochemical markers of bone turnover in a patient with osteoporosis should lead to further investigation of other causes of low bone mass or fracture as osteoporosis is not generally characterized by high bone turnover, except in early postmenopausal women whose bone turnover often is high. Where the responsiveness of bone turnover markers to many different factors makes them less good at predicting long‐term outcomes such as fractures, it makes them better for monitoring interventions—pharmacological and to some extent nonpharmacological . Bone resorption markers and subsequently bone formation markers respond quickly to antiresorptive therapy and remain suppressed during effective antiresorptive therapy.…”
mentioning
confidence: 99%